HCV Self-Testing to Expand Testing: A Pilot Among Men Who Have Sex With Men in China - Xu, Wenqian; Reipold, Elena Ivanova; Zhao, Peizhen; Tang, Weiming; Tucker, Joseph D.; Ong, Jason J.; Wang, Jinshen; Easterbrook, Philippa; Johnson, Cheryl Case; Jamil, Muhammad S.; Wang, Cheng (Frontiers in Public Health, 2022)
Background Hepatitis C virus self-testing (HCVST) may increase test uptake especially among marginalized key populations such as men who have sex with men (MSM). We conducted an observational study to assess the usability, acceptability and feasibility of HCVST among MSM in China. Methods An observational study with convenience sampling was performed among MSM in Guangzhou, China in 2019. The OraQuick® HCV Rapid Antibody Test kits were used in this study. Participants performed all 12 HCVST steps and interpreted the results in the presence of a trained observer. Usability was defined as the number and percentage of participants who completed all testing steps correctly without assistance and interpreted the results correctly. Inter-reader concordance was calculated as the percentage agreement between the results interpreted by the participant and those interpreted by a trained staff member. The same process was used to estimate inter-operator agreement between the self-testing and professional use test results. Acceptability was assessed using an interviewer-administered semi-structured questionnaire. Results Among 100 participants with median age 27 (interquartile range 23–30) years, 4% reported prior history of HCV testing, 41% reported using blood-based HIV self-testing in the past, 54% (95%CI: 43.7–64.0%) completed all self-testing steps correctly without assistance and interpreted the results correctly. Both the inter-reader and inter-operator concordance were excellent at 97% (95%CI: 91.5–99.4%) and 98% (95%CI: 93.0–99.8%), respectively. The majority rated the HCVST process as very easy (52%, 95%CI: 41.8–62.1%) or easy (41%, 95%CI: 31.3–51.3%), 76% (95%CI: 66.4–84.0%) were willing to use HCVST again, and 75% (95%CI: 65.3–83.1%) would recommend it to their family and friends. Conclusions Our findings demonstrate that oral fluid HCVST has high usability and acceptability among Chinese MSM. More implementation research is needed to plan how best to position and scale-up HCVST alongside other facility-and community-based testing approaches and ensure data linkage into health systems.